Mechanical properties and damage characterization of cracked granite after cyclic temperature action - Xiankai Bao; Lingyu Wang; Guangqin Cui; Jianlong Qiao; Baolong Tian; Shunjia Huang; Lizhi Wang (Scientific Reports)
Abstract Due to the unique geographical environment of the plateau, large-scale damage and destruction of fractured surrounding rock often occur during geotechnical engineering construction as a result of high-temperature cycles. Therefore, this study aims to investigate the mechanical properties and damage characteristics of fractured granite under the influence of cyclic temperature, uniaxial compression tests were conducted on granite specimens with pre-existing fractures at cyclic temperatures of 30 °C, 50 °C, 70 °C, 100 °C, and 130 °C. The study integrated analyses of characteristic stress, acoustic emission parameters, damage variables, fractal dimensions, and SEM to explore the mechanical properties and damage features of granite. The results indicated that at a 45° fracture inclination and a temperature of 70 °C, granite exhibited a distinct turning point in mechanical properties and damage characteristics. At the same cyclic temperature, granite with a 45° pre-existing fracture showed significant decreases in peak stress, elastic modulus, and σci/σm ratios, with the AE b-value drop point noticeably earlier, and both cumulative AE ring count and total energy reduced. The damage variable quickly reached its maximum, and the development of internal microcracks in the specimen is highly orderly. At the same fracture inclination, peak stress, elastic modulus, and σci/σm slightly increased at 70 °C, while AE ring counts and total energy were lower, indicating the degree of internal thermal damage in the specimen has significantly decreased, and the development of internal microcracks in the specimen has shown a marked reduction in orderliness. These findings provide theoretical insight into the meso-damage and failure mechanisms of granite influenced by different cyclic temperatures and fracture inclinations.